(3TQM GdJUQja GdYRis - (3eaQL Hf CHi GdMSf Hf eaQL GdCHQRis; (3GdRfLGfj , YHO GdhgGH Hf EHQGgje Hf YHO GdhgGH GdNRQLj, YRGdOjf CHh GdaVGFd,J (B655 (3g` s ((3eMeO Ydi Hf TcQ Gddg s)
(3ChdgG (B:s
(3hHYO ajbhd GdYHO GdCHQRi deG cGf GdeNJUQ aiYde GdUQa GdefShH Edi GdEeGe GdRfLGfi s
(3BNQgG (B:s
(3ddaQb Hjfg hHjf GdeQI , Je s
(3GdYRi ai GdJUQja GfXQ cTa GdXfhf L(B2 (3U` (B1139s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdUQas